Pengaruh Kompetensi dan Pengembangan Karir Terhadap Kepuasan Kerja Dengan Komitmen Organisasi Sebagai Variable Intervening Pada PT. Karya Hevea Indonesia Dolok Masihul - Sri Winda Hardiyanti Damanik; Fanny Lus Utami; Suripto Moh Zulkifli (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
This study aims to determine the effect of competence, and career development, on job satisfaction with organizational commitment as an intervening variable at Pt. Hevea Indonesia's Dolok Masihul. This type of research is explanatory research that explains the causal relationship between variables through hypothesis testing. This study used a sample of 42 respondents. Sampling used purposive sampling technique. The data collection technique used a questionnaire which was then processed with SPSS 25.00. Based on the results of research that has been carried out by researchers, it can be concluded that competence has no effect on organizational commitment, career development does affect organizational commitment, competence affects job satisfaction, career development affects job satisfaction, organizational commitment does not affect job satisfaction, Based on the results of the indirect effect of 0.0236 < direct effect of 0.475, it can be said that the sixth hypothesis is rejected, which means organizational commitment does not mediate the relationship between competence (X1) on job satisfaction , Based on the results of the indirect effect of 0.0361 < the direct effect of 0.427, it can be said that the seventh hypothesis is rejected, which means that organizational commitment does not mediate career development on job satisfaction .